Numerical modelling and parametric analysis of bond strength of masonry members retrofitted with FRP - Maruccio, Claudio (2014)
The paper discusses the bond between fibre-reinforced polymer (FRP) strips and brick masonry, using advanced non-linear simulations of experimental test results. The context of the research is the study of the interfacial behaviour of a brittle substrate (masonry) and a thin elastic addition (the FRP) used as a strengthening system for historical structures. Moreover, to further validate the numerical results, the problem is also approached analytically. In the numerical model, the interface is represented with zero-thickness finite elements, with inelastic behaviour fully formulated using the incremental plasticity theory. The mechanical characterization of the materials involved and the local interfacial behaviour allowed defining the main parameters and the constitutive law to be adopted. Based on the experimental results, the detailed finite element model is calibrated so that it is possible to describe the bond phenom- enon at the local level up to failure, identifying the strain and slip distribution, the local bond stress peak and its migration along the bond length for flat and curved layers. Numerical results and analytical pre- dictions show a good agreement with experimental data, allowing to provide a comprehensive discussion on the bond behaviour. Moreover some differences between interfacial behavior of FRP–masonry/concrete joints are highlighted. Finally applications of the model to analyze strengthened structural components (such as masonry arches) are provided.